The epidemiology and pathogenesis of coronavirus disease (COVID-19) outbreak. Issue 109 (May 2020) - Rothan, Hussin A.; Byrareddy, Siddappa N.
Abstract: Coronavirus disease (COVID-19) is caused by SARS-COV2 and represents the causative agent of a potentially fatal disease that is of great global public health concern. Based on the large number of infected people that were exposed to the wet animal market in Wuhan City, China, it is suggested that this is likely the zoonotic origin of COVID-19. Person-to-person transmission of COVID-19 infection led to the isolation of patients that were subsequently administered a variety of treatments. Extensive measures to reduce person-to-person transmission of COVID-19 have been implemented to control the current outbreak. Special attention and efforts to protect or reduce transmission should be applied in susceptible populations including children, health care providers, and elderly people. In this review, we highlights the symptoms, epidemiology, transmission, pathogenesis, phylogenetic analysis and future directions to control the spread of this fatal disease. Highlights: Coronavirus disease (COVID-19) represents global public health concern and WHO declares public health emergency. The phylogenetic analysis revealed that COVID-19 is potentially a zoonotic virus. Special attention is necessary to protect or reduce transmission in susceptible populations. COVID-19 develop intestinal symptoms like diarrhea, while low percentage of MERS-CoV or SARS-CoV patients had diarrhea. Identification of novel chemotherapeutic drugs for treating COVID-19 infections is urgently warranted.